2019
DOI: 10.3389/fphar.2019.01463
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound-Sensitive Liposomes for Triggered Macromolecular Drug Delivery: Formulation and In Vitro Characterization

Abstract: Mistletoe lectin-1 (ML1) is a nature-derived macromolecular cytotoxin that potently induces apoptosis in target cells. Non-specific cytotoxicity to normal cells is one of the major risks in its clinical application, and we therefore propose to encapsulate ML1 in a nanocarrier that can specifically release its cargo intratumorally, thus improving the efficacy to toxicity ratio of the cytotoxin. We investigated the encapsulation of ML1 in ultrasound-sensitive liposomes (USL) and studied its release by high-inten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 31 publications
0
21
0
Order By: Relevance
“…The presence of unsaturated acyl chains phospholipids and PEG-Lipopolymers improves the susceptibility of vesicle bilayers to low frequency ultrasound. The ultrasound-responsive liposomes were also prepared by different lipids in combination with perfluorocarbon DPPC/cholesterol/DSPE-PEG 2000 [153]. Some phosphatidylcholinebased lipids as well as other phospholipids used in ultrasound-triggered drug release from liposomes have been discussed here.…”
Section: Sound-responsive Lipidsmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of unsaturated acyl chains phospholipids and PEG-Lipopolymers improves the susceptibility of vesicle bilayers to low frequency ultrasound. The ultrasound-responsive liposomes were also prepared by different lipids in combination with perfluorocarbon DPPC/cholesterol/DSPE-PEG 2000 [153]. Some phosphatidylcholinebased lipids as well as other phospholipids used in ultrasound-triggered drug release from liposomes have been discussed here.…”
Section: Sound-responsive Lipidsmentioning
confidence: 99%
“…Frenkel and coworkers demonstrated that high-frequency intensity-focused ultrasound is an advanced non-invasive technique for targeted treatment by focusing a high energy focal point as well as high-frequency ultrasonic beams within the body [95]. Matos et al, 2019 [153], prepared ultrasound-responsive liposomes using various lipid ratios of DPPC/cholesterol/DSPE-PEG 2000 and studied its release by high-intensity focused ultrasound (HIFU). Ultrasound-responsive liposomes were fabricated by mixing nanodroplets of perfluorocarbon (PFC) with pegylated liposomes.…”
Section: Sound-responsive Lipidsmentioning
confidence: 99%
“…Heat [ 54 ] induced a phase transition in the lysolipid-containing lipid membrane leading to bilayer destabilization and pore formation, and the ML-I could leave the cargo [ 55 ]. Secondly, ultrasound [ 56 ] also induced a disruption (cavitation) of the lipid bilayer, releasing the contents [ 57 ]. Since the formulation in ultrasound-sensitive liposomes (USL) showed the triggered release of over 90% compared to 10% release from temperature-sensitive liposomes (TSL), USL are therefore a promising approach, despite the complex purification procedure and the initial losses of the encapsulated cargo.…”
Section: Phospholipids In Research—project Overviewmentioning
confidence: 99%
“…For example, when applying sonothrombolysis, a technology that dissolves blood clots in blood vessels by causing cavitation using ultrasound, the use of MNB can lower the ultrasonic energy for cavitation. This reduces the burden on the patient when dissolving blood clots [ 17 ] and internal drugs can be released using cavitation [ 18 ]. Additionally, the combination of ultrasound (US) and bubble can increase drug permeability to BBB, with delivering antisense to BBB using US and bubble as an example [ 19 ].…”
Section: Introductionmentioning
confidence: 99%